Etika Bisnis Islam - Mutiara Manalu; Nazwa Alpuja Elsa; Gymnasti Febriani (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Islamic business ethics are moral values ​​and rules that govern business activities within the framework of Islamic teachings. This study aims to achieve justice, integrity and honesty as well as balance and prosperity for all parties involved. The problem that occurs is that companies in Indonesia have not yet fully implemented business ethics in running the company. The research method used is library research, by collecting and analyzing data from various sources such as journals, books, and related articles. The results of the analysis show that Islamic business ethics refers to the main sources of Islamic teachings, namely the Qur'an and Hadith, which provide guidelines on how humans should interact fairly and ethically in economic transactions. In the perspective of Islamic law, there are basic principles that must be avoided in doing business, namely: not containing elements of usury, not containing elements of fraud and not doing business with prohibited goods. In conclusion, understanding and applying the principles of basic values ​​of honesty, justice, and mutual benefit and benefits for their business. This not only provides benefits for the company in the long term, but also has a positive impact on society and the surrounding environment. Thus, Islamic business ethics become a strong foundation in managing business sustainably and building a just and prosperous society.